Seasonal Variation of Metal Concentration in Barnacles (Balanus spp.) of Cochin Estuary, South West Coast of India - Ashraf. P., Muhamed; B., Meenakumari; Thomas, Saly N (Fishery Technology, 2025)
The studywas conducted to evaluate the accumulation of heavymetals in barnacle shells and tissues in different seasons of the year. Heavy metal concentration was monitored in barnacle tissues and shells on a long term and short term (monthly) basis by exposing glass panels in Cochin estuary. Short term panels gave a clear idea of the dynamics of heavy metal accumulation in barnacles. Accumulation of chromium and cadmiumwasmaximum in the tissues and shell during themonsoon season whereas lead and nickel was maximum in pre monsoon period. Selenium varied irregularly and arsenicwas detected only in one sample. Higher levels of copper andmanganese were observed in shells during both high and low salinity season (pre monsoon and monsoon). Manganese and iron uptake was significantly higher in the initial stages of growth and is mainly utilized for shell formation. Zinc was maximum during monsoon in short term panels whereas in soft tissues of long term panels it was detected during monsoon and pre monsoon seasons. Fouling settlement on exposed glass panels was highest during November, the transition period from monsoon to post monsoon season.